A Character Study of the Fiction "Toba Tek Singh" - Ilyas, Uswa; Qandeel, Bazghah (sourcecoder, 2024)
Saadat Hasan Manto is an all-round personality of Urdu literature. Manto appeared in the literary world as a translator, sketch writer, fiction writer, dramatist, essayist and letter writer and showed his skills in every genre but who The genre immortalized Manto’s name forever. He was the most popular genre of prose literature, fiction. Manto is the milestone of Urdu fiction. Our fiction tradition is more natural than Saadat Hasan Manto, unreserved, unique, internal. And there is no mythicist with such inexplicable power. At the thematic level, there is a lot of diversity in Minto. In terms of themes, Minto’s fictions are based on psychological, political and social issues. He has also written openly on the subject of freedom riots, prostitutes and sexual problems. He has also written numerous fictions on the riots. He also includes the collective events and problems that arose during the independence of the subcontinent in stories. He also tries to solve common human problems. Initiation also deals with the physical changes that occur during puberty. He also sheds light on psychological facts. Therefore, many aspects of life are the subjects of his fictions. Minto’s perfect art is that he made the subject alive and immortal. Thus, the realities and bitterness of the entire era became part of his fictions.